Positive and negative mood states mediated the effects of psychological resilience on emotional stability among high school students during the COVID-19 pandemic - Han, Fulei; Wang, Qiulin (Frontiers in Psychology, 2022)
This study investigated the parallel mediating effects of positive and negative mood states on the relationship between psychological resilience and emotional stability among first- through third-year senior high school students in China during the challenges of the COVID-19 pandemic. Of 408 questionnaires distributed from April 11 to April 22, 2022, to students at a high school located in Changzhou, Jiangsu, China, 360 were completed correctly and analyzed using a cross-sectional study design. The questionnaire included items from the modified Chinese version of the Psychological Resilience Scale, the Profile of Mood States scale, and the Eysenck Personality Questionnaire Short Scale in Chinese, the latter to assess emotional stability. The mediating effects of mood states on the relationship between psychological resilience and emotional stability were explored by using structural equation modeling and bootstrapping methods. The results indicated that psychological resilience directly affected emotional stability but also indirectly affected emotional stability through the mediating effects of positive and negative mood states. The mediating effect of negative mood states was greater than that of positive mood states. This result differs from that of research conducted prior to the pandemic, which found that compared with the damage caused by negative moods to emotional stability, positive moods more strongly promoted emotional stability. Our findings indicate that high school officials in China should consider strengthening mental health support for students who are taking courses online during home quarantine.